The Influence Of Students' Perceptions Of Arabic Language Teacher Creativity On Motivation For Learning Arabic Class XI Madrasah Aliyah Jamilurrahman Yogyakarta - Takdir Kamaludin; Farih Muzaky (IJAS: International Journal of Arabic Studies, 2024)
This study aims to determine the creativity of Arabic teachers in the learning process, students' motivation to learn Arabic, and the influence of teacher creativity on students' motivation to learn Arabic at Madrasah Aliyah Jamilurrahman Yogyakarta. This research uses a quantitative approach with a correlational field research design. Data collection was conducted through questionnaires and documentation, and analyzed using product moment analysis. The results of the study show: (1) The creativity of Arabic teachers at Madrasah Aliyah Jamilurrahman Yogyakarta is in the medium category with a score of 68.80%, which is classified as positive. (2) The majority of class XI students' motivation to learn Arabic is in the weak category, although a few students have strong motivation. (3) There is a positive and significant influence between teacher creativity (X) and students' motivation to learn Arabic (Y) in class XI, with a calculated r value of 0.335 and a table r value of 0.3120 at a 5% significance level. This indicates that the more creative the teacher is in teaching, the higher the students' motivation to learn.